2022
DOI: 10.1155/2022/7942727
|View full text |Cite|
|
Sign up to set email alerts
|

An Epidemiological Study on the Relationship between Drug Control Program and Patient Compliance in Elderly Patients with Hypertension

Abstract: Objective. To explore the relationship between medication control regimen and patient compliance in elderly hypertensive patients. Methods. A retrospective analysis of 1432 elderly hypertensive patients in our hospital from February 2020 to February 2021 was conducted. The general data of patients, the drug control regimen, the occurrence of drug side effects, and blood pressure control of patients during hospitalization and outpatient follow-up were statistically analyzed. Results. The first dose rate was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%